Near-Infrared Spectroscopy-Based Frontal Lobe Neurofeedback Integrated in Virtual Reality Modulates Brain and Behavior in Highly Impulsive Adults - Hudak, Justin; Blume, Friederike; Dresler, Thomas; Haeussinger, Florian B.; Renner, Tobias J.; Fallgatter, Andreas J.; Gawrilow, Caterina; Ehlis, Ann-Christine (Frontiers in Human Neuroscience, 2017)
Based on neurofeedback (NF) training as a neurobiological treatment in attention-deficit/hyperactivity disorder, we designed a randomized, controlled functional near-infrared spectroscopy (fNIRS) NF intervention embedded in a virtual classroom in which participants controlled overhead lighting with their dorsolateral prefrontal brain activation. We tested the efficacy of the intervention on healthy adults displaying high impulsivity as a sub-clinical population sharing common features with ADHD. Twenty participants, ten in experimental and ten in a shoulder muscle-based electromyography control group, underwent eight training sessions across two weeks. Training was bookended by a pre- and posttest including go/no-go, n-back, and Stop-signal tasks. Results indicated a significant reduction in commission errors on the no-go task with a simultaneous increase in prefrontal oxygenated hemoglobin concentration for the experimental group, but not for the control group. Furthermore, the ability of the subjects to gain control over the feedback parameter correlated strongly with this reduction in FA errors for the experimental, but not for the control group, indicating the potential importance of learning feedback control in moderating behavioral outcomes. In addition, participants of the fNIRS group showed a reduction in reaction time variability on the stop-signal task. Results indicate a clear effect of our NF intervention in reducing impulsive behavior possibly via a strengthening of frontal lobe functioning. Virtual reality additions to conventional NF may be one way to improve the ecological validity and symptom-relevance of the training situation.